SPEECH DEVELOPMENT OF CHILDREN WITH DYSARTHRIA BASED ON COOPERATIVE EDUCATIONAL TECHNOLOGY - Dilnavoz Rakhmatova (Journals Park Publishing, 2024)
Cooperative education is aimed at organizing the educational process more effectively, and since the improvement of children's literacy begins directly in the preschool education organization, it is explained that it is in the preschool education organization that some elements of cooperative education can be used.
Keywords: education, cooperation, technologies, methodology, information, team, training, speech, assignment, opportunity, applause, music, download.